Videography Training: Improving the Soft Skills of the Young Generation Through Digital Content - Rachmat, Rachmat; Yusuf, Muhammad; Faisal, Faisal; Asia, Siti Nur; Suherwin, Suherwin; Basmar, Muh. Fahmi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
The development of digital technology and social media has created great opportunities for young people to develop videography skills as valuable soft skills. This community service activity aims to improve the videography skills of young people in East Luwu Regency through digital content creation training. The implementation method includes theoretical training on the basics of videography, hands-on practice using equipment, and video editing workshops. The activity was carried out for 3 days involving 30 participants from youth and students in East Luwu Regency. The results of the activity showed a significant increase in participants' understanding of shooting techniques, video composition, and basic editing. Pre-test and post-test showed an increase in average scores from 45.2 to 78.6. Participants successfully produced 15 quality short videos showcasing the tourism and cultural potential of East Luwu. This activity has a positive impact in developing creativity and digital capabilities of young people, and has the potential to open creative economy opportunities in the region. Follow-up activities are needed to maintain and develop the abilities that participants have acquired.